A Critique of an Epistemic Intellectual Culture: Cartesianism, Normativism and Modern Crises. (24th February 2015) - Arponen, V. P. J.
Abstract: The so‐called epistemological turn of the Descartes‐Locke‐Kant tradition (Rorty) is a hallmark of modern philosophy. The broad family of normativism constitutes one major response to the Cartesian heritage building upon some version of the idea that human knowledge, action and sociality build fundamentally upon some form of social agreement and standards. Representationalism and the Cartesian picture more generally have been challenged by normativists but this paper argues that, even where these challenges by normativism have been taken to heart, our intellectual culture remains fundamentally epistemic in certain problematic senses. Two problems are highlighted: first, normativism remains functionally Cartesian, for human action and sociality appear as processes driven by the shared understandings by competent contributors (regardless of how these are constructed naturalistically), and second, normativism is unable to account for forms of human action and sociality other than those occurring in the relatively small worlds of normatively regulated conceptual spaces of mutual access and listening. These points are illustrated by an applied discussion of the blind spots of normativist accounts of the emerging environmental and the on‐going economic crises.